Crebanine, an aporphine alkaloid, sensitizes TNF-α-induced apoptosis and suppressed invasion of human lung adenocarcinoma cells A549 by blocking NF-κB-regulated gene products - Supachai Yodkeeree (2018)
© 2014, International Society of Oncology and BioMarkers (ISOBM). Crebanine is an alkaloid known to exhibit anticancer, but its mechanism is not well understood. Besides, the nuclear factor-kappa B (NF-κB) transcription factor has been correlated with inflammation, carcinogenesis, tumor cell survival, invasion, and angiogenesis. In this study, we investigated the effects of crebanine on tumor necrosis factor alpha (TNF-α)-induced NF-κB activation and the expression of NF-κB-regulated gene products. We found that crebanine reduced the cell proliferation of lung, ovarian, and breast cancer cells. Crebanine also potentiated TNF-α-induced apoptosis which correlated with the suppression of the gene products linked to cell survival, B cell lymphoma-extra large, and proliferation, cyclin D1. In addition, crebanine affected TNF-α-induced activation of caspase-8, caspase-3, and poly(ADP-ribose) polymerase cleavage, indicating that the apoptotic effects of TNF-α were enhanced by crebanine. Moreover, crebanine reduced TNF-α-induced A549 cell invasion and migration. Furthermore, crebanine suppressed the TNF-α-mediated expression of proteins that involved cancer cell invasion (matrix metalloproteinase 9 urokinase-type plasminogen activator, urokinase-type plasminogen activator receptor and intercellular adhesion molecule 1) and angiogenesis (COX-2 and VEGF), all of which are known to be regulated by NF-κB. We also demonstrated that TNF-α induced NF-κB DNA-binding activity, which was inhibited by crebanine. Moreover, crebanine suppressed the TNF-α-induced degradation of inhibitor of NF-κB alpha (IκBa), which led to reduced NF-κB translocation to the nucleus. Taken together, our results demonstrated that crebanine reduced TNF-α-induced cancer cell proliferation, invasion, and survival by suppressing NF-κB activity and expression profile of its downstream genes.